Earliest Arrival Evacuation Planning: Two-Terminal Case - Sah, Ram Uday; Khadka, Shree Ram (Journal of Advanced College of Engineering and Management, 2016)
Evacuation planning problem can be considered as a dynamic flow problem on the dynamic network. In a dangerous situation, as many individuals as possible should be rescued from a dangerous zone to a safety zone as quickly and efficiently as possible. The earliest arrival flow problem is to send a maximal amount of dynamic flow reaching the safety zone sink not only for the given time horizon, but also for any earlier moment of the time horizon. In this paper we discuss the optimization formulation of the earliest arrival evacuation planning problem with efficient solution procedure. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, page: 57-62